TYPES OF SURGERY AND BREAST RECONSTRUCTIONS PERFORMED ON PATIENTS TREATED BY THE BRAZILIAN UNIFIED HEALTH SYSTEM AT PÉROLA BYINGTON HOSPITAL - Aquino, Renata Borges; Gebrim, Luiz Henrique; Mattar, Andre; Shida, Jorge Yoshinori (Mastology, 2021)
Introduction: Breast cancer is the most frequent cause of cancer death in women, also haunting them because surgical treatment can vary from expanded resection to mastectomy, causing aesthetic, functional, psychological and social damage. In Brazil, where 70% of the population is treated through the Unified Health System (SUS) and about 55% of cases are treated in advanced stages, most patients undergo mastectomy without immediate reconstruction. However, occa- sional mammographic screening carried out in some large cities has led to an increase in the number of diagnoses in the initial stages and, thus, a decrease in mortality from breast cancer, in addition to the possibility of less radical surgical treatments. Due to the scarcity of data in this population, we decided to perform an observational study at our institution. Objectives: This work aims at characterizing the types of surgical treatment that patients with breast cancer were submitted to at the Women’s Health Reference Center (CRSM) at Hospital Pérola Byington in São Paulo, SP, from 2015 to 2019 and the breast reconstructions carried out from January 2015 to December 2019. Methods: This is a retrospective, descriptive, observational study performed through the review of medical records of patients followed up at our service. Inclusion criteria were female patients diagnosed with malignant breast cancer treated with conservative and radical surgery, with or without immediate and late reconstruction in this 5-year period. Results: At CRSM, from 2015 to 2019, 9,097 surgical procedures were performed for the treatment of breast cancer. Radical surgeries represented 53.5%, with 2% of adenectomies. Regarding conservative surgeries, there were 4,222 procedures, 43.4% of which were quadrantectomies. From January 2015 to December 2019, 4,902 breast reconstructions were performed, 17.8% of which were immediate. Conclusions: Our data also showed 51.5% of patients underwent mastectomy due to the predominance of tumors in stages II and III. However, about 47% of patients were treated conservatively for their efforts to reduce the time to diagnosis, palpable lesions and the occasional screening performed in the city of São Paulo, resulting in a proportion of 46.5% of the patients who underwent conservative surgery. Breast reconstruction was performed in 46.8% of mastectomies, with only 82.4% being in a late stage.